Gene polymorphism of CYP2C19*2, *3 and CYP3A4*1B and early stent thrombosis: case reports and literature review. (September 2016) - Kulmyrzaeva, Nazgul; Tatarunas, Vacis; Skipskis, Vilius; Smagulova, Gaziza; Seitmaganbetova, Nazgul; Veikutiene, Audrone; Lesauskaite, Vaiva
We present two clinical cases of acute and subacute coronary artery stent thrombosis in patients treated at the Department of Interventional Cardiology in Aktobe, Kazakhstan. Our results draw attention to the impact of CYP3A4*1B on the clinical effect of clopidogrel during dual antiplatelet therapy after PCI. The genotyping performed at the Laboratory of Molecular Cardiology of Institute of Cardiology of Lithuanian University of Health Sciences in Lithuania revealed that both patients were homozygous carriers of CYP3A4*1B*1B . They also were carriers of CYP2C19 loss-of-function *2 or *3 alleles ( *1*2 and *1*3, respectively).